2015
DOI: 10.1371/journal.pone.0130658
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective Signature of Short-Term Caloric Restriction

Abstract: ObjectiveTo understand the molecular pathways underlying the cardiac preconditioning effect of short-term caloric restriction (CR).BackgroundLifelong CR has been suggested to reduce the incidence of cardiovascular disease through a variety of mechanisms. However, prolonged adherence to a CR life-style is difficult. Here we reveal the pathways that are modulated by short-term CR, which are associated with protection of the mouse heart from ischemia.MethodsMale 10-12 wk old C57bl/6 mice were randomly assigned to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 88 publications
1
42
0
1
Order By: Relevance
“…The astonishingly potent effect of calorie restriction (CR) on AKI was confirmed by a more recent study from our group . Similar results have been reported in other models of renal injury (eg, cisplatinum‐induced AKI) and in other organ systems . Although a short‐term diet has been proven to be feasible and safe in patients undergoing living‐donor kidney transplantation, no prospective trials have been undertaken to investigate the possible impact of moderate CR as an organ‐protective measure.…”
Section: Introductionsupporting
confidence: 79%
“…The astonishingly potent effect of calorie restriction (CR) on AKI was confirmed by a more recent study from our group . Similar results have been reported in other models of renal injury (eg, cisplatinum‐induced AKI) and in other organ systems . Although a short‐term diet has been proven to be feasible and safe in patients undergoing living‐donor kidney transplantation, no prospective trials have been undertaken to investigate the possible impact of moderate CR as an organ‐protective measure.…”
Section: Introductionsupporting
confidence: 79%
“…Reports have indicated that caloric restriction (CR) attenuates the development of cardiomyopathy and decline in heart function normally associated with aging 12. Moderate CR decreases visceral fat and blood pressure and improves the lipid profile, glucose uptake, and insulin sensitivity, and hearts from CR rodents show an improved ischemic tolerance 1316. Furthermore, CR preserves pancreatic mass and function by suppressing apoptosis in the db/db mouse,17 attenuates the development of hepatic steatosis in the db/db mice,18 and decreases adiposity in the genetically hyperphagic OLEFT model of type 2 diabetes 19.…”
Section: Introductionmentioning
confidence: 99%
“…Since high levels of Fet A are correlated with higher levels of TLR2 expression at adipocyte level, this means that high Fet A level is related to inflammation during metabolic syndrome as manifested by TLRs activation [23]. It has been proved on experimental models that chronic FAs release stimulated TLR4 on adipocytes, leading to increased production of inflammatory adipokines, including interleukin-6 (IL-6), tumor necrosis factor-a (TNF-a), and monocyte chemoattractant protein-1 (MCP-1), consequently leading to increased monocyte accumulation, giving rise to impaired insulin sensitivity [24, 25]. Cohen et al demonstrated that TLR2/4, FFAs, and Fet A are increased during diabetic cardiomyopathy, but there is possibility to achieve a significant improvement of these biomarkers through a short period of caloric restriction, with a consequent therapeutic potential [24].…”
Section: Overview On Mechanisms Involved In Diabetic Heart Diseasementioning
confidence: 99%